Cloud Computing: BDaaS and HDaaS (Big Data as a Service and Hadoop as a Service) - Agarwal, Ujjwal (International Journal of Computer Sciences and Engineering, 2025)
Two technologies currently change the world and most important for organizations: Cloud Computing and Big Data. Data is everywhere; this data is generated by the organization, people and machine. Insight analysis of this data is most important. Cloud computing provide the services for storage, process and analysis of this large and complex data sets that can create competitive advantage, spark new innovations. The main objective of this paper to describe the concepts of big data, cloud computing, Big Data as a Service (BDaaS) and Hadoop as a Service (HDaaS) on cloud platform. . Apache Hadoop is an open source software framework to store and analysis of Big Data. Demo IBM Ambari Console is used to demonstrate the working architecture of Big Data Hadoop on Cloud platform. Focusing on Infrastructure as a service, platform as a Service and Software as a Service in terms of Big Data model.